Dynamic processes in the oil pipelines. Part II. The leak identification by numerical methods - Bajoraitytė, Ingrida; Bogdevičius, Marijonas (Transport, 2003)
The analysis of identification method of leaks occurring due to damages of the linear part of the main oil pipelines is carried out. The momentum and continuity equations of viscous compressible fluid in a pressure pipeline are presented. Differential equations of fluid movement in the oil pipeline are solved by the method of characteristics. Variation diagrams of pressure and velocity of fluid of a leaking oil pipeline are presented. First Published Online: 19 Dec 2011